Formation features of warm period floods on the rivers of Mountain Crimea - Прокофьев, О. М.; Овчарук, В. А.; ТодороваE. И. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2015)
The article analyzes the conditions of floods formation in the warm period on the rivers of Crimean Mountains. To illustrate the water regime of the rivers in the considered area the runoff hydrographs with pronounced floods in warm period have been built. Their analysis allowed us to determine that the floods of the warm period of the year on the rivers are not observed at one time: on the rivers of the western part of the northern slope of the Crimean Mountains maximum discharges of the warm period are observed more often in April and July; on the rivers of the southern coast of Crimea - from April to August, and on rivers of the eastern part of the northern slope - in the spring. In Crimea, 80-85% of the annual precipitation falls as rain. The number of days with rainfall ranges from 80-130 in the steppe regions to 150-170 – in the mountains. In the summer in the Crimea there are no more than 5-10 days with rains in the month. On the rivers of Mountain Crimea rainstorms are causing flooding accompanied by destruction of eroded rocks. In fact, in heavy rainfall not water – but a mix of earth and stones are flowing. Such flows destroy bridges, wash away roads, the fertile soil layer. Rainstorms never cover the entire Crimea. They typically fall in any one area. Most often heavy rains and downpours occur within one day and only in winter are possible within a few days. Generalization of data on the distribution of the maximal rainfall of warm period have revealed that the most frequently observed maximum rainfall of 71-90 mm (27.3%) is also typical of the formation of floods in warm season rainfall in the range of 31-70 mm (the sum frequency of their occurrence is 40.9%). Rainfall forming floods tend to increase with the height of the watershed, but the coefficient of this relationship is not significant. Our study has allowed to determine that a material effect on runoff in the period of catastrophic floods have factors such as karst, watershed area and forested.